ACC Deaminase Producing Bacteria With Multifarious Plant Growth Promoting Traits Alleviates Salinity Stress in French Bean (Phaseolus vulgaris) Plants - Gupta, Shikha; Pandey, Sangeeta (Frontiers in Microbiology, 2019)
Plant growth promoting rhizobacteria (PGPR) with 1-aminocyclopropane-1-carboxylate (ACC) deaminase activity has potential to promote plant growth and development under adverse environmental conditions. The present study describes the isolation of six bacteria displaying ACC deaminase activity (from 900 to 1800 nmol α-ketobutyrate mg protein-1 h-1) from rhizospheric soil of Garlic (Allium sativum) crop. Out of six, two were selected for evaluation of other plant growth promoting activities. Apart from ACC deaminase activity (more than 1500 nmol α-ketobutyrate mg protein-1 h-1), these two isolates ACC02 and ACC06 exhibited production of Indole acetic acid (greater than 30 μg/ml), siderophore, ammonia, Hydrogen cyanide as well as solubilized insoluble form of phosphates (exceeding 85 mg/ml) and zinc. Besides presence of multifarious plant growth promoting activities these two isolates were also tolerant to salinity stress up to 4% (ACC02 up to 6%) and drought stress of 0.05MPa (ACC06 up to 0.73 MPa). The molecular characterization of isolates ACC02 and ACC06 on the basis of 16S rRNA gene sequencing revealed that they belong to the genus Aneurinibacillus and Paenibacillus, respectively. The growth promoting abilities of these isolates were evaluated in pots by bio-priming French bean (Phaseolus vulgaris) seeds. The results of this study revealed that treatment of bacterial isolates in the form of consortia significantly improved the (P≤ 0.05) morphological and physiological parameters than the individual treatment of the under salinity stress (25mM NaCl) conditions. The consortia treatment augmented the increment in root length (110%), root fresh weight ( 45%), shoot length (60%), shoot fresh weight (255%) and total chlorophyll content ( 57%) as compared to uninoculated positive control under salinity stress conditions.